The experiences of nursing master's students with dialogic case-based learning in an evidence-based nursing course: A qualitative study - Yao, Jiannan; Zhang, Xiuying; Xue, Hui; Zhu, Mingyue; Wang, Jia; Wang, Qiuchen; Chen, Zhiming; Yuan, Hua (Nurse education today, 2022)
Evidence-based nursing (EBN) is a complex subject for teachers and students due to the abstract concepts involved. It requires combining theory with practice and is included in the major courses required for a master's education in many countries. Case-based learning (CBL), which is a student-centred teaching method, has been widely used in numerous disciplines because it can bridge the gap between theory and practice and foster critical thinking and communication skills. However, to adapt CBL to EBN coursework for a Master of Nursing degree, improve evidence-based practice (EBP) and enhance core competencies, the case design and operational procedures of CBL need to be further examined. To explore nursing master's students' experiences of dialogic CBL and case design and operational procedures regarding dialogic CBL. A descriptive–qualitative study design was used. The study was carried out in the nursing master's programme at a university in China. Twenty first-year nursing master's students who completed a 10-week EBN course were recruited using purposive sampling. Data were collected between September and December 2020 via in-depth semistructured interviews. The data were analysed using thematic analysis. Four themes were identified: (1) ‘learning theoretical EBN knowledge’; (2) ‘improving clinical nursing ability’; (3) ‘enhancing core competencies’; and (4) ‘barriers to implementing dialogic CBL’. The study provided a standardised CBL procedure based on students' experiences, which included preparation, group discussions, presentations, and teachers' feedback following the presentations, and these operational procedures were shown to be indispensable. The student experiences in this study should be referenced by nursing educators who apply this teaching method in other graduate and undergraduate nursing courses such as surgical nursing and nursing research.